2006
DOI: 10.1111/j.1600-0838.2006.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Sports‐related eye injuries: floorball endangers the eyes of young players

Abstract: The objectives of this study were to determine the distribution of different sports-related eye injuries and to identify injury types to enable recommendations to be made about the use of protective eyewear. The study population comprises all 565 eye trauma patients examined at the Ophthalmology Emergency Clinic of the Helsinki University Central Hospital over a 6-month period. Data were collected from patient histories and questionnaires. In addition, three severe floorball eye injury cases are presented. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 9 publications
1
34
1
2
Order By: Relevance
“…Our study showed that the percentage of sport eye inju- ries on the territory of the city of Belgrade of 3.6% was significantly less in comparison to percentage of the same injuries reported by other authors [3][4][5][6][7]. There are several reasons for the aforementioned.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Our study showed that the percentage of sport eye inju- ries on the territory of the city of Belgrade of 3.6% was significantly less in comparison to percentage of the same injuries reported by other authors [3][4][5][6][7]. There are several reasons for the aforementioned.…”
Section: Discussioncontrasting
confidence: 46%
“…Canavan et al in 1980 reported the incidence of sport eye injures of 4.1% [4], and Jones, in 1988, showed the increase of percentage to 25.1% [5], while in MacEwen's paper, 1989, the proportion of sport eye injures was 42.2% [6]. At the beginning of 21st century such percentage was decreased, and therefore, Barr et al, in their study in 2000, reported the sport eye injury incidence of 12.5% [2], and in 2007 study by Len et al, such percent was 11% [7]. This paper analyzes the incidence, nature of injury and functional sequelae of sport injuries in Serbia in the first decade of our century.…”
Section: Introductionmentioning
confidence: 96%
“…In the current study period, protective eyewear was mandatory in the under-14 age group. In the current study (6-month time period), the number of floorball eye injuries in the under-14 age group was one compared to 11 in the previously published study , in an equal 6-month time period) (Leivo et al 2007); the sole floorball eye injury in the under-14 age group was incurred during a non-organised practice.…”
Section: Sportmentioning
confidence: 85%
“…As the latter (Leivo et al 2007) data set was collected for a 6-month period, and many sports are to some extent seasonal, the comparison was performed for an equal, 6-month time period, 3.12-3.6. 95% confidence intervals and a chi-square distribution test were used for statistical analysis of incidence rate differences.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation